2021
DOI: 10.22219/jinop.v7i1.14250
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi pendidikan karakter berbasis kearifan lokal

Abstract: The integration of local wisdom, such as batik and glass painting, and other Cirebon culture in general courses (Mata Kuliah Umum/ MKU) may be an interesting alternative learning approach. This research aims to describe the implementation of character education models based on local cultural wisdom such as the ability to design batik, glass paintings, and the introduction of other typical Cirebon cultures in MKU. It employed a descriptive qualitative approach to explore naturally visible phenomena. The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 12 publications
1
10
0
18
Order By: Relevance
“…The qualitative research findings are consistent with (HB, 2006) assertion that qualitative research produces a detailed and in-depth description of the condition portrait of what occurred according to the subject being studied. Sugiyono; Faiz & Soleh, 2021) revealed that qualitative research can observe certain phenomena that are felt by research subjects empirically including behavior, perceptions, motivations and actions. A consensus was reached that the participating teachers would also create their research questions relevant to their students and their teaching situations.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative research findings are consistent with (HB, 2006) assertion that qualitative research produces a detailed and in-depth description of the condition portrait of what occurred according to the subject being studied. Sugiyono; Faiz & Soleh, 2021) revealed that qualitative research can observe certain phenomena that are felt by research subjects empirically including behavior, perceptions, motivations and actions. A consensus was reached that the participating teachers would also create their research questions relevant to their students and their teaching situations.…”
Section: Methodsmentioning
confidence: 99%
“…Dalam penelitian ini analisis data berlangsung saat pengumpulan data melalui rangkaian observasi dan wawancara kepada subjek penelitian untuk memperoleh jawaban yang kredibel (Miles & Hubberman, 1992). Adapun teknik pengumpulan data mengambil teori (Sugiyono, 2013: 337;Faiz & Soleh, 2021) yang terdiri dari proses reduction (reduksi data), data display (penyajian data), dan data conclusion drawing/ verification (penarikan kesimpulan). Berikut gambar alur penelitian yang dipilih pada penelitian ini: Gambar 2.…”
Section: Metode Penelitianunclassified
“…In a study, (Hidayati et al, 2021) suggested that in order to strengthen Indonesian local character learning, the values of local wisdom must be increased in character learning. In this case, Faiz and Soleh (2021) found one of the characters that grows and develops to create creative abilities in sustaining life through entrepreneurial activities.…”
Section: The Term Of Local Wisdom In Learning Cycle Managementmentioning
confidence: 99%